Survivors’ perceptions regarding the follow-up of pain complaints after breast cancer treatment: Distinct coping patterns - Slaghmuylder, Yaël; Lauwerier, Emelien; Pype, Peter (Frontiers in Psychology, 2023)
After finishing cancer treatment, breast cancer survivors often experience both physical and psychosocial symptoms such as pain. In some, pain can persist for months or even years. Pain is a complex experience. Its occurrence and maintenance are explained through interactions between multiple factors, which are biological/physiological, psychological, and social in nature. Unaddressed needs related to this problem - such as insufficient pain relief, limited validation of the problem, and minimal physical and psychological support - may cause severe disability and negatively impact well-being and quality of life. This study investigated how breast cancer survivors perceive their (chronic) pain complaints to be addressed during follow-up care. Furthermore, we explored how they coped with the way their trajectories happened to unfold. We conducted four focus groups with a total of thirty-one breast cancer survivors. Each focus group consisted of an asynchronous part with an online discussion platform and a synchronous part through video calls. Data analysis was guided by the Qualitative Analysis Guide of Leuven. Narratives revealed the unmet needs of survivors and showed variability in the lived experiences of having to deal with pain. Some survivors tend to ignore the pain, while others look for solutions to reduce pain. A third coping pattern is accepting pain and its impact. Furthermore, how survivors cope with pain is influenced by intrapersonal, interpersonal, and societal processes. For example, pain-related beliefs and prejudices among healthcare providers, family, friends, colleagues, other cancer survivors, and society could possibly steer a survivor towards a certain way of coping. In these processes, the role of healthcare providers seems pivotal. For instance, when survivors do not feel heard or taken seriously by healthcare providers, their acceptance of pain can be impeded. To conclude, a person’s way of coping with pain and the associated needs is dynamic and influenced by factors at multiple levels such as the intrapersonal, interpersonal and societal level. To sufficiently address the problem of pain among cancer survivors, we therefore also need actions that tackle the health care system and its stakeholders, as well as the public debate concerning cancer follow-up care.